1996
DOI: 10.1139/a96-016
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric emissions and depositions of cadmium, lead, and zinc in Europe during the period 1955–1987

Abstract: This paper presents a preliminary estimate of atmospheric emissions of cadmium, lead, and zinc in Europe during the period 1955–1987. The emission data were used as input to the atmospheric transport model TRACE (trace toxic air concentrations in Europe) of the International Institute for Applied Systems Analysis, to compute cumulative deposition loads of heavy metals onto European soils during the investigated time period. The maxima of cumulative depositions computed with the TRACE model over the entire peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 6 publications
2
13
1
1
Order By: Relevance
“…Similar comparison made by other research groups (e.g., Olendrzynski et al 1996) for Zn seems to indicate an accuracy within a factor of 2. In general, the Zn data are often underestimated due to incomplete knowledge of emission sources.…”
Section: Quality Of Emission Estimatessupporting
confidence: 89%
See 1 more Smart Citation
“…Similar comparison made by other research groups (e.g., Olendrzynski et al 1996) for Zn seems to indicate an accuracy within a factor of 2. In general, the Zn data are often underestimated due to incomplete knowledge of emission sources.…”
Section: Quality Of Emission Estimatessupporting
confidence: 89%
“…During the last two decades there has been great progress in defining major anthropogenic sources of Cd, Pb, Hg, and other trace metals in Europe and in other parts of the world (Pacyna et al 1995;Olendrzynski et al 1996;Pirrrone et al 1996;Pacyna and Pacyna 1999). It was concluded that hightemperature processes, such as coal and oil combustion in electric power stations and heat and industrial plants, gasoline combustion, roasting and smelting of ores in non-ferrous metal smelters, melting operations in ferrous foundries, refuse incineration, and kiln operations in cement plants emit various trace metals, which enter the atmosphere and the aquatic and terrestrial ecosystems.…”
Section: Two Decades Of Emission Inventorying For Trace Metalsmentioning
confidence: 99%
“…NRIAGU (1989) a été le premier à tenter de quantifier l'importance relative des sources naturelles et anthropiques à l'échelle globale, mais il a été confronté à des lacunes importantes dans les données de base. Le sujet demeure important et plusieurs autres chercheurs ont repris les calculs de NRIAGU, parfois à l'échelle globale (GARRETT, 2000;PACYNA et al, 1995;PACYNA et al, 2006), mais souvent pour des régions spécifiques ou pour certains métaux individuels (OLENDRZYNSKI et al, 1996;RICHARDSON et al, 2003). Ces analyses démontrent clairement que les activités anthropiques ont perturbé les cycles géochimiques de plusieurs métaux, dont Ag, Cd, Cu, Hg, Ni, Pb et Zn.…”
Section: Sources De Métauxunclassified
“…More recent data for the 1980s can be found in Pacyna and Graedel (1995) and for the beginning of the 1990s, in Pacyna (1998). A study that is very interesting to compare with this work was done by Olendrzynski et al (1996). They give a historical overview of the atmospheric emissions and depositions (although still preliminary) of Cd, Pb, and Zn in Europe during the period 1955-1987.…”
Section: Global and European Trace Metal Emission Inventoriesmentioning
confidence: 99%